Perubahan Mood Mahasiswa saat Kuliah Sudah Mulai Offline - Rita Markus Idulfilastri; Frangky Franscois (Syntax Corporation Indonesia, 2024)
Changes in mood are a factor in dealing with increased stress during the Covid-19 pandemic. The importance of mood control in everyday life has an impact on measurements on psychological measurement tools that measure a person's mood. Measurement is considered difficult to measure because naturally mood is abstract and too diverse to be categorized. The purpose of this study was to validate the use of the Four Dimensional Mood Scale (4DMS) with a sample of Indonesian students. The participants involved in this study amounted to 50 people consisting of 40% women and 60% men. Analysis used Exploratory Factor Analysis (EFA) with Promax rotation and Confirmatory Factory Analysis (CFA). The results show that there are five factors that appear to understand the factors of mood changes that students have, namely